Comparativo de patrones climáticos entre los años 1981 al 2000 y 2001 al 2020 y fluctuaciones hidrológicas del río Amazonas Loreto 2024 - Romero Villacrez, Juan Luis (2024)
The research work was carried out in Iquitos, in 2024, with a quantitative methodology, explanatory research level, correlational type and predictive level with retrospective data; aimed to compare the climatic pattern of the twentieth century of the last 20 years vs. the climatic pattern of the present century of the first 20 years of the twenty-first century, and the hydrological fluctuations of the Amazon River. The results report that there are significant differences between the patterns of temperatures, relative humidity and rainfall, in the period of the last century and in the present century, as well as with the fluctuations of the Amazon River. The correlation in the 21st century is much weaker than in the 20th century, which would indicate a change in dynamics, where the minimum temperature affects the fluctuations of the river. Regarding the relative humidity variable, the correlation in the 21st century is stronger than in the 20th century, which indicates that relative humidity could have a greater influence on river fluctuations in the 21st century. Regarding rainfall, a weak but significant correlation in both periods, denotes a consistent but limited relationship between precipitation and river fluctuations.